Neurochemical Characterization of the Tree Shrew Dorsal Striatum - RICE, MATTHEW W.; ROBERTS, ROSALINDA C.; MELENDEZ-FERRO, MIGUEL; PEREZ-COSTAS, EMMA (Frontiers in Neuroanatomy, 2011)
The striatum is a major component of the basal ganglia and is associated with motor and cognitive functions. Striatal pathologies have been linked to several disorders, including Huntington's, Tourette's syndrome, obsessive-compulsive disorders and schizophrenia. For the study of these striatal pathologies different animal models have been used, including rodents and non-human primates. Rodents lack on morphological complexity (for example, the lack of well defined caudate and putamen nuclei), which makes it difficult to translate data to the human paradigm. Primates, and especially higher primates, are the closest model to humans, but there are ever-increasing restrictions to the use of these animals for research. In our search for a non-primate animal model with a striatum that anatomically (and perhaps functionally) can resemble that of humans, we turned our attention to the tree shrew. Evolutionary genetic studies have provided strong data supporting that the tree shrews (Scadentia) are one of the closest groups to primates, although their brain anatomy has only been studied in detail for specific brain areas. Morphologically, the tree shrew striatum resembles the primate striatum with the presence of an internal capsule separating the caudate and putamen, but little is known about its neurochemical composition. Here we analyzed the expression of calcium-binding proteins, the presence and distribution of the striosome and matrix compartments (by the use of calbindin, tyrosine hydroxylase and acetylcholinesterase immunohistochemistry), and the GABAergic system by immunohistochemistry against glutamic acid decarboxylase and Golgi impregnation. In summary, our results show that when compared to primates, the tree shrew dorsal striatum presents striking similarities in the distribution of most of the markers studied, while presenting some marked divergences when compared to the rodent striatum.